Nilai-nilai Hak Asasi Manusia dalam Kasus Peradilan Ṭu‘Mah bin Ubairiq pada Masa Rasulullah: Human Rights Values in the Case of Ṭu‘Mah Ibn Ubairiq during the Prophetic Era - Adhyputra, Muhammad Fadel; Akbar, Muhammad Raihan (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
Judicial practices in many Muslim countries today still show inequality and unfair treatment, especially towards minority groups and those who are socially and economically disadvantaged. This disparity highlights the need to revisit Islamic history in order to revive the universal values of justice that form the basis of the Islamic legal and judicial systems. This study aims to analyze the case of Ṭu‘mah Bin Ubairiq during the time of the Prophet Muhammad saw. in order to identify reflections of human rights values. This study uses a qualitative method with a historical-normative approach and Mashood A. Baderin's interdependence theoretical framework, which emphasizes the complementary relationship between Sharia and human rights as two normative systems with the same goal of ensuring justice and human dignity. This article analyzes primary sources of Islamic law and uses the UDHR as a comparative framework. The results of the study show that the resolution of the Ṭu‘mah case strongly reflects the fundamental principles of the UDHR, such as equality before the law (Article 7), the right to a fair trial (Article 10), the presumption of innocence (Article 11), and the protection of property rights (Article 17) and honor (Article 12). It can be concluded that despite originating from different sources of legitimacy, this case demonstrates that universal human rights principles have long been internalized in the Islamic judicial tradition based on divine revelation.